Sharing the land: the formation of the Vancouver Island (or 'Douglas') Treaties of 1850-1854 in historical, legal and comparative context - Vallance, Neil (2015)
Chapter I introduces the Vancouver Island or ‘Douglas’ Treaties of 1850-54, entered into between several Vancouver Island First Nations and Hudson’s Bay Company Chief Factor, James Douglas, acting as agent of the Crown. The written versions purported to extinguish the aboriginal title of the First Nations to their land. Recent research has indicated that these documents do not accurately reflect what was agreed between the parties at the treaty meetings. The goal of the dissertation is to ascertain the likely terms of the treaties. This task also posed my major research challenge, as very little contemporaneous documentation exists of the formation of the treaties. There are a number of first- and second-hand accounts reduced to writing long after the events described, but they have received little attention from scholars until now. Chapter II is devoted to a critical analysis and comparison of the extant First Nation and colonial accounts, from which I conclude that the treaties were likely agreements by the First Nations to share not cede their land. Chapter III makes a comparison with first person accounts of the Washington or ‘Stevens’ Treaties of 1854-55, entered into between vii viii Native American tribes and the United States government. I conclude that these accounts bolster the likelihood that the Vancouver Island agreements were sharing treaties. Chapter IV follows up on a fascinating connection between the written versions of the Vancouver Island Treaties and an agreement concerning land between the Ngai Tahu Moari of New Zealand’s south island and Henry Kemp, acting as agent of the Crown. The comparison provides a number of useful contrasts and parallels with the Vancouver Island Treaties. Chapter V describes the silencing of the Vancouver Island Treaties by the policies of successive governments, the inattention of scholars and the decisions of Canadian courts. Finally, Chapter VI reviews existing and potential categories of historical treaties between First Nations and the Crown. By analogy with ...